Speech Functions and Prepositional Phrases on Shampoo Slogans - Angelina Kusuma Jelita Mawarni; Barli Bram (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This article investigated speech functions and prepositional phrases on shampoo slogans. The objectives of this study were to explore the types of speech functions and to examine prepositional phrases on picture shampoo slogans. The data, consisting of 56 shampoo slogans and 11 picture shampoo slogans, were collected from the internet. The method was descriptive qualitative. Results showed that the statement occurred 52 times (92.85%), command, thrice (5.35%), and question once (1.78%). Afterwards, 11 pictures of shampoo slogans were analyzed to categorize speech functions. The findings showed three speech functions, namely a statement, question, and command. The percentages were the statement (81.81%) and command (18.18%). The types of prepositional phrases were analyzed based on the 56 shampoo slogans. The percentages were "for" (29.03%), "of" (24.19%), "to" (17.74%), then "with" (12.90%), "as" (3.22%), "in, about" (3.22%), and "from" (1.61%).